Gastric plication surgery changes gastrointestinal and metabolic parameters in an obesity-induced high-fat diet model - Machado, Mariana Pirani Rocha [UNESP]; Gama, Loyane Almeida; Beckmann, Ana Paula S.; Pinto, Leonardo Antônio [UNESP]; de Miranda, José Ricardo de Arruda [UNESP]; Marques, Rozemeire Garcia [UNESP]; Américo, Madileine Francely (Wiley, 2024)
Background: Obesity treatment includes less invasive procedures such as gastric plication (GP) surgery; however, its effects on gastrointestinal (GI) motility parameters are underestimated. We aimed to verify the metabolic and gastrointestinal effects of GP surgery in the rat obesity model. Methods: A high-fat diet-induced obesity was used. Animals were allocated to four experimental groups: control sham (n = 6); control GP (n = 10); obese sham (n = 6); and obese GP (n = 10). Nutritional and murinometric parameters, gastric motility, glucose tolerance, histopathology, fat depots, leptin, and lipoproteins levels were evaluated 30 days after surgery. Data were analyzed by ANOVA followed by post Tukey or Kruskal–Wallis test followed by Dunn's multiple comparisons test. Key Results: Gastric plication decreased leptin levels, feed efficiency, and body weight gain. GP does not improve lipid profile in obese animals and however, ameliorates glucose tolerance in control and obese rats. GP did not improve the gastric emptying time or normalize the frequency of contractions disturbed by obesity. Surgery provides a remodeling process in the mucosa and muscularis mucosa layers, evidenced by leukocyte infiltration mainly in the mucosa layer. Conclusions & Inferences: Our study revealed the influence of the gastrointestinal tract on obesity is underestimated with pieces of evidence pointing out its important role as a target for surgical treatment.
Keywords: bariatric surgery; gastrointestinal tract; high-fat diet; western diet